2016
DOI: 10.1002/rcs.1743
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery rapidly and successfully implemented in a high volume laparoscopic center on living kidney donation

Abstract: Left-sided robot-assisted donor nephrectomy is feasible with over time a significant decrease in operative time with good outcomes for donor and recipient. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
2
36
1
3
Order By: Relevance
“…Janki et al [9] showed a significant improvement in total operative time after 60 RADNs performed, indicating the importance of the learning curve in RADN.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Janki et al [9] showed a significant improvement in total operative time after 60 RADNs performed, indicating the importance of the learning curve in RADN.…”
Section: Resultsmentioning
confidence: 99%
“…The series presented by Janki et al [9] showed that left-sided RADN is safe and feasible with good outcomes for donor, recipient, and graft survival after 3 months of follow-up. The RADN procedure might take longer; however, 3D imaging, better instrument movement, and comfort are gained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations